A world of cities - Murray, Lily (Walker Studio, 2017)
"From Amsterdam, Berlin and Barcelona, to Tokyo, New York and Shanghai, visit places you have only dreamed of in this elegant celebration of cities from all over the world. Explore each one through James Brown's beautiful illustrations, unlock a miscellany of intriguing facts and bring personality of each city to life"--Back cover
Keywords: Cities and towns / Juvenile literature; Cities and towns / History / Juvenile literature; Cities and towns; History; Juvenile works; Bilderbuch